Strategi Partnership pada Bisnis Aneka Keripik dalam Menembus Pasar Global - Nadita Sari; Moh. Rois Abin (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
In the current era of globalization, the economic field has an increasing influence on trade activities. The existence of economic needs that tend to be the same throughout the world, a local business has the opportunity to be able to expand its market share to the global market. One of the strategies that can provide opportunities for businesses to increase their business in an increasingly competitive business world is the partnership strategy. This research will analyze the partnership strategy applied by the various chips business at PT Nadasuka Gunung Budheg in penetrating the global market. The research was conducted using descriptive qualitative research methods with the aim of analyzing the phenomena that occur in the field. The results showed that in penetrating the global market, PT Nadasuka Gunung Budheg implements a partnership strategy with a supply chain pattern through mutual exports. The strategy of building partnerships is done with commitment, choosing the right partner, mutual trust, communication, and discipline. In maintaining a sustainable partnership relationship, it is done by maintaining product quality, offering product variants, good service, and conducting regular evaluations. This research provides an overview of how to build a partnership strategy to maintain the competitive advantage of a business in both local and global markets.